Batas Usia Perkawinan dan Dispensasi Nikah sebagai Upaya Perlindungan Perempuan dan Anak di Indonesia : Marriage Age Limit and Marriage Dispensation as Efforts to Protect Women and Children in Indonesia - Dwi Husniyati; Muhamad Faqih; Ahmad Pahrul Pauji; Humaeroh (Litera Academica Publishing, 2026)
Marriage, also known as matrimony, is both a fundamental right and a basic need for humans as social beings who cannot live in isolation. In practice, the state sets a minimum age for marriage to prevent child marriage and protect women and children. This article aims to discuss regulations regarding the minimum age for marriage, marriage dispensations, and legal protections for women and children in Indonesia. The method used in writing this article is the library research method, which involves collecting data and information from literature sources such as books, scientific journals, and laws and regulations related to the minimum age for marriage, marriage dispensations, and legal protection for women and children. The results of the discussion indicate that legal protection for women and children is implemented through restrictions on the marriage age specifically, setting the minimum age at 19 years for both men and women the application of the best interests of the child principle in the marriage dispensation process, and various laws and regulations concerning child protection. The regulation of the marriage age limit aims to protect women and children from the impacts of early marriage. However, marriage dispensations remain a factor in the occurrence of child marriage, so better legal protection and oversight are needed in the process of granting marriage dispensations.